Quantitative phosphoproteomic analysis reveals common regulatory mechanisms between effector‐ and PAMP‐triggered immunity in plants. Issue 4 (5th November 2018) - Kadota, Yasuhiro; Liebrand, Thomas W. H.; Goto, Yukihisa; Sklenar, Jan; Derbyshire, Paul; Menke, Frank L. H.; Torres, Miguel‐Angel; Molina, Antonio; Zipfel, Cyril; Coaker, Gitta; Shirasu, Ken
Summary: Plant immunity consists of two arms: pathogen‐associated molecular pattern (PAMP)‐triggered immunity (PTI), induced by surface‐localized receptors, and effector‐triggered immunity (ETI), induced by intracellular receptors. Despite the little structural similarity, both receptor types activate similar responses with different dynamics. To better understand phosphorylation events during ETI, we employed a phosphoproteomic screen using an inducible expression system of the bacterial effector avrRpt2 in Arabidopsis thaliana, and identified 109 differentially phosphorylated residues of membrane‐associated proteins on activation of the intracellular RPS2 receptor. Interestingly, several RPS2‐regulated phosphosites overlap with sites that are regulated during PTI, suggesting that these phosphosites may be convergent points of both signaling arms. Moreover, some of these sites are residues of important defense components, including the NADPH oxidase RBOHD, ABC‐transporter PEN3, calcium‐ATPase ACA8, noncanonical Gα protein XLG2 and H + ‐ATPases. In particular, we found that S343 and S347 of RBOHD are common phosphorylation targets during PTI and ETI. Our mutational analyses showed that these sites are required for the production of reactive oxygen species during both PTI and ETI, and immunity against avirulent bacteria and a virulent necrotrophic fungus. We provide, for the first time, large‐scale phosphoproteomic data of ETI, thereby suggesting crucial roles of common phosphosites in plant immunity. Abstract : See also the Commentary on this article by Adachi & Tsuda, 221 : 1676–1678 .